KOMUNITAS PHYTOPLANKTON DAN PRODUKTIVITAS PRIMER DANAU SELAIS KAMPUS BINA WIDYA UNTUK RANCANGAN HANDOUT BIOLOGI SMA - Destiranda, Eko; Suwondo, Suwondo; Ahmad, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the phytoplankton community andprimary productivity as the quality of watering, as well as to produce a handout designas teaching materials in biology learning in class X SMA. This research was conductedin July-August 2020 in the waters of Danau Selais, Bina Widya Campus, RiauUniversity and the Laboratory of Biology Education, FKIP, Riau University. This studyused 2 designs, namely using a survey method with the steps as descriptive quantitativein data collection and handout design. The parameters measured include physical,chemical and biological parameters. The sampling of phytoplankton communities was 4points of observation with 3 samples, while the primary productivity was carried out bythe dark-light bottle method. 18 species of phytoplankton in the waters of Danau Selais,Bina Widya Campus, Riau University and 719 individuals. The abundance ofphytoplankton ranges from 22453.20-985444.60 ind / liter which indicates that thewaters of Selais Lake are categorized as moderate fertility waters with good waterquality. The phytoplankton diversity index value ranged from 2.30 to 3.61 and theevenness value of phytoplankton was 0.53-0.62 which indicates that the phytoplanktonin Selais Lake was quite even. The primary productivity of Danau Selais at Bina WidyaCampus reaches Eutrophic fertility levels of 1,010.38 mgC / m3 / day. The parametersof Lake Sealis chemical physical factors include temperature ranging from 28.7-29.10C, pH of water ranging from 6.55-6.63, brightness level of 46 cm and total suspendedsolid, namely 18-22 mg / L. Based on the potential analysis, the results of the study weredesigned to be handouts as teaching materials on ecosystem materials for Biologylearning in class X SMA.Key Words: Phytoplankton Community, Primary Productivity, Biological Handout Design